2021
DOI: 10.1111/radm.12477
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the role of risk‐taking in innovation: antecedents and effects

Abstract: This study addresses innovation development with a focus on risk-taking, widely considered a relevant driver for the exploration and exploitation of new ideas. The study empirically examines the effects of risk-taking propensity on innovation performance and its antecedents. We consider the role of several key antecedents related to the organizational structure and the activities of firms aimed at encouraging employees to take risks in innovation. We performed an empirical survey within a global and innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 65 publications
0
14
0
1
Order By: Relevance
“…For example, using the example of a group operating in more than 70 countries, it was proven that risk-taking has an impact on innovation performance. It was further indicated that clearly defined innovation goals, cooperation, innovation support activities, and availability of organizational resources positively determine risk-taking (Giaccone & Magnusson, 2022). A study of Chinese companies found that risk-taking indirectly affects the relationship between digital transformation and innovation (Liu et al, 2023).…”
Section: Appendixmentioning
confidence: 99%
“…For example, using the example of a group operating in more than 70 countries, it was proven that risk-taking has an impact on innovation performance. It was further indicated that clearly defined innovation goals, cooperation, innovation support activities, and availability of organizational resources positively determine risk-taking (Giaccone & Magnusson, 2022). A study of Chinese companies found that risk-taking indirectly affects the relationship between digital transformation and innovation (Liu et al, 2023).…”
Section: Appendixmentioning
confidence: 99%
“…According to Hult et al (2004), innovation involves upgrading products, processes, or procedures to improve an organization's performance (Bhupendra and Sangle, 2022;Ranjan and Nayak, 2023). The relationship between innovation and performance has also been extensively studied in organizations operating in various sectors (Akg€ un et al, 2014;Carlos Pinho, 2008;Giaccone and Magnusson, 2022). However, it has been limited in the context of SaaS companies operating in an emerging economy such as India.…”
Section: Innovativeness and Corporate Successmentioning
confidence: 99%
“…Considering collaborating among partners with different expertise is a practical approach to improving the reliability of the innovation process [38], a myriad of studies have examined the rules of enterprise collaboration with various types of institutions, such as universities [39,40], customers, and suppliers [41], so as to understand how to control the collaboration process and what are the major factors that drive the successes and failures of such innovation endeavors [42]. However, significant hurdles remain in the implementation process, including the lack of close cooperation among partners [43], unstable operation, and low success rate [44], and existing research does not provide an effective method to evaluate the collaboration process.…”
Section: The Governance Of Cipmentioning
confidence: 99%